Políbio Alves entre contos e encantos: o fascínio do vivido na perspectiva da escrita de si - Córdula, Ana Cláudia Cruz (2015)
Personal archives are understood as memory narrative territories able to express an organization´s or individual´s life journey, so the current piece of research is based on the personal archive, still unexplored, of the writer, from Paraíba, PolíbioAlves. As the scope is to constructhis literate, cultural and social trajectory under the perspective of self-writing, it intends to reveal the writings of a trajectory by establishing a relation of meanings and discoveries which enables us to attribute to it an autobiographic value. Therefore, as methodological foundation the qualitative research of documental type will be adopted, being associated with the oral history of life as method. The survey carried out, so far, leads us to a declaration of a writer with his own characteristics, being unique in his writing, a real letter craftsman. PolíbioAlves writes beyond his works enabling the writing of his “selves” by means of his personal archive, between the lines of the “already-said” and the “not-said”. From this perspective, it tries to understand the weaving of the selection and organization of the archive, as project of the self.